Communication Challenges in the Eve of the 4.0 Industrial Revolution - VOINA, Andreea Nicoleta; PAVELEA, Anișoara (2022)
Communication challenger in the eve of the 4.0 industrial revolution is a comprehensivevolume including papers presented within the International Students’ Conference onCommunication, organized by the Department if Communication, Public Relations andAdvertising, Faculty of Political, Administrative and Communication Sciences, Babes-BolyaiUniversity, Cluj-Napoca, Romania, between the 26th and the 27th of April 2018. The topics of thepapers are related to nowadays communication science and reflect upon the interests of the currentstudents in communication science majors.